(untitled) (Research, Society and Development, 2018)
The constant oscillations in society and the labor market require the management professional to evolve and develop their competencies, organizations are looking for people who are capable and flexible, who adapt quickly to changes. In this way, developing competencies has become paramount in the learning process, and higher education institutions play an important role in this construction, applying learning strategies that provide the academic with the competencies demanded by the market. Thus, it is feasible to use active learning in the Administration course, since it allows the integration between theory and practice and the experience of real situations in the classroom. Active learning is a set of pedagogical practices that address the issue of student learning from a different perspective of the classic learning techniques. In active learning, it is understood that the student should not be merely a receiver of information, but must actively engage in the acquisition of knowledge. This article aims to identify and analyze the skills of the Administrator desired and developed by the undergraduate students in Administration in the context of Active Learning. In this study, a descriptive research was carried out in a sample of 54 students from the Administration courses of three universities in Santa Catarina. Among the results, the research revealed that for students, the most important competences to be developed are: self-criticism and strategic thinking regarding opportunities.